The cycle of abuse: emotional availability in resilient and non-resilient mothers with early life maltreatment - Mielke, Emilia Louisa L.; Neukel, Corinne; Fuchs, Anna; Spieß, Karen; Zietlow, Anna-Lena; Bertsch, Katja; Reck, Corinna; Möhler, Eva; Herpertz, Sabine (Psychopathology, 2020)
Background: Early life maltreatment (ELM) has a high risk of transmission across generations, known as "the cycle of abuse." ELM is also an important risk factor for developing mental disorders, and having a mental disorder increases the risk of child abuse. Both the abuse potential in mothers with ELM and in mothers with a history of mental disorders might be associated with a disturbed mother-child interaction. Objective: The current study examined differences in emotional availability between mothers with a history of ELM and previous or current mental disorders (non-resilient), mothers with ELM without mental disorders (resilient), and control mothers without ELM and without mental disorders. Methods: Thirty-three non-resilient mothers, 18 resilient mothers, and 37 control mothers and their 5- to 12-year-old children participated in a standardized mother-child interaction task. Videotaped interactions were rated by three independent, trained raters based on the Emotional Availability Scales (EA Scales) and compared between the groups. Results: The non-resilient mothers and their children showed reduced maternal sensitivity, structuring, non-intrusiveness, non-hostility, responsiveness, and involvement compared to the resilient mothers and their children and the control mothers and their children (p = 0.006, eta(2)(p) = 0.12). No differences on any of the EA Scales were found between resilient mothers and control mothers. Conclusions: These deficits in mother-child interaction in non-resilient mothers might contribute to mechanisms that could explain the cycle of abuse. Interestingly, resilient mothers, who did not develop a mental disorder despite having experienced ELM, did not show these deficits. Thus, prevention programs promoting resilience might be a key to break the cycle of abuse.
Gesehen am 18.01.2021